(untitled) (ModaPalavra e-periódico, 2018)
This paper addresses the contribution from Emotional Design to Surface Design. By considering the Donald Norman’s Three Levels of Design theory (2008), it describes the Van Gogh-Roosegaarde cycle path, Holland. Results point to the use of luminescent materials as an interactive resource between the surface-medium, besides causing emotional impact to users as it modifies the urban landscape in a sustainable way. The conceptual aspects and the technical resources that have guaranteed the success of the project are demonstrated. In addition, it is concluded that the phosphorescent paint was critical to satisfy the three levels of design, which characterizes a good project.